O potrzebie kształcenia technicznego w odbudowie niepodległej Polski w przekazie „Przeglądu Technicznego” z lat 1914-1918 - Michalski , Grzegorz (Studia Edukacyjne, 2019)
After the outbreak of the Great War, a discussion on the role of the school system in the reconstruction of the independent Polish state started in the Warsaw-based Stowarzyszenie Techników Polskich (Association of Polish Technicians). The research on the contents of Przegląd Techniczny (Technical Review), which was a magazine published by that organization, shows that the editors saw the relationship between professional education and industrial development of the state, free from restrictions imposed by the invaders, and, as a result, published notes and articles to convince the society about the need to educate teenagers in occupational schools. Thus, they informed the readers on the operation of schools of that type and various initiatives and forms of technical education and improvement, most of all in Warsaw. They also presented their own projects in that area. Supporting the organization of the technical education system, they proposed three-year lower occupational schools for professional education of workmen, secondary schools educating “intelligent technicians adapted to the needs of the industry”, and higher technical schools conferring a title of the engineer on their graduates.